Students' video viewing habits during a flipped classroom course in engineering mathematics - Kjetil Liestøl Nielsen (Association for Learning Technology, 2020)
A flipped classroom lecture approach was utilised in an engineering mathematics course (118 students). This article reports on student viewing habits based on 104 videos over a period of 12 weeks. The video statistics indicate that many students waited until the last day before assignments to watch the required videos. There are also indications that the students would try to reduce the heavy workload induced by watching all videos on a single day by skipping videos perceived as less valuable. The data show a strong negative correlation between the length of a video and how much of that video the students watched per viewing setting. However, although students watched less of longer videos, the data also indicate that the students still watched, to a large degree, every part of the videos, just not in a single viewing session. Based on these results, recommendations on video creation and flipped classroom implementation are given.